Вироби з кістки та рогу з Малого городського городища - Сергєєва М.С., М.С. (Археологія і давня історія України, 2020)
До наукового обігу вводяться матеріали з обробки кістки та рогу з Малого городища давньоруського м. Городськ, які зберігаються у Наукових фондах ІА НАНУ. Надано аналіз виробів, техніку їх виготовлення і визначено рівень розвитку косторізного ремесла. The materials of bone processing from the Small Hillfort of Horodsk (the Korostyshiv Region of the Zhytomyr Oblast) stored in the Institute of Archeology of NAS of Ukraine are published in the paper. The analysis of the products, technique of manufacture and level of development of bone-carving craft is provided. Bone artefacts include the completed products, blanks and bone raw material with traces of processing. Bone artifacts come from the cultural layer and the objects dated to two periods: the 12th — first half of the 13th centuries and the second half of 13th—14th centuries.